Formation of `single walled' TiO2 nanotubes with significantly enhanced electronic properties for higher efficiency dye-sensitized solar cells - Mirabolghasemi, Hamed; Liu, Ning; Lee, Kiyoung; Schmuki, Patrik (Chemical Communications, 2013)
The present work establishes a process for the anodic growth of self-organized TiO2 nanotubes with a single-walled morphology. This yields not only a much more defined tube geometry but also provides a significant increase in properties and prospect for a wide range of TiO2 nanotube applications.
EAM Import::2019-03-14